Repurposing of Polio Vaccine in Prevention of COVID-19: Thinking towards more options - Awanish Kumar; Sunil Kumar; Dharmendra Pandey (ACHSM, 2022)
COVID-19 has created an unprecedented crisis worldwide in every sector. There currently is no approved drug available against this disease. The development of a vaccine is also a complex and long process that is often completed in 10-15 years. Recently, several vaccines for COVID-19 have received emergency approval for use but few experts deem that currently approved COVID-19 vaccines might provide a temporary boost to the immune system but they are dubious for their long-term effect and safety. This article sheds light on polio vaccine as a possibility on COVID-19 prophylaxis because this vaccine was developed through a rigorous process of the various phases of development. The polio vaccine could provide another option to combat COVID-19 and if we have more options, we can fight more effectively against the pandemic. The polio vaccine is utilized globally with a highly satisfactory retort and very good immune responses. By seeing a satisfactory cross-protective immune response, the polio vaccination could be repurposed and offered against COVID-19 for an effective immuno-prophylaxis and protection. This article focusses on the repurposing of vaccines/drugs for COVID-19 and discusses the scientific rationale behind the suggestive use of the polio vaccine against COVID-19 because the polio vaccine is FDA-approved less expensive, readily available, easy to administer, and highly safe.